Genomic Analysis and Stability Evaluation of the Phenol-Degrading Bacterium Acinetobacter sp. DW-1 During Water Treatment - Gu, Qihui; Chen, Moutong; Zhang, Jumei; Guo, Weipeng; Wu, Huiqing; Sun, Ming; Wei, Lei; Wang, Juan; Wei, Xianhu; Zhang, Youxiong; Ye, Qinghua; Xue, Liang; et al. (Frontiers in Microbiology, 2021)
Phenol is a toxic organic molecule that is widely detected in the natural environment, even in drinking water sources. Biological methods are considered to be a good tool for phenol removal without secondary pollution. In this study, genomic information of a phenol-degrading bacterium (Acinetobacter sp. DW-1) with high phenol degradation ability at low and high concentration was analysed. The genome size of Acinetobacter sp. DW-1 was 4.13 Mb. The contigs were then assembled into two scaffolds with an average length of 4,134,434 bp. A total of 3859 unigenes with an average length of 933 bp were obtained. A KEGG pathway analysis suggests that Acinetobacter sp. DW-1 could utilise phenol via the β-ketoadipate pathway, including the catechol and protocatechuate branches. Subsequently, a bio-enhanced polyhedral hollow polypropylene sphere (BEPHPS) filter was constructed to investigate the stability of the seeded bacteria during the water treatment process for 56 days. The biofilm on the BEPHPS was observed using SEM and CLSM. The denatured gradient gel electrophoresis (DGGE) profile indicates that when the BEPHPS filter was operated for 56 days, except for band 1 (namely Acinetobacter sp. DW-1), the other three indigenous bacteria (bands 2, 3, and 4) persisted and became the dominant bacteria in the treatment group’s BEPHPS. In addition, 16S rRNA gene amplicon sequencing results indicate that Acinetobacter sp., Pseudomonas sp., Nitrospira sp., and Rubrivivax sp. were the predominant bacteria in the treatment group. This study advances the current understanding of the phenol degradation mechanism of Acinetobacter sp. and provides new insights into the stability of seeded bacteria during water treatment.